Construcción europea y conformación del espacio público europeo - López Gómez, Carlos; Pereira Castañares, Juan Carlos; Neila Hernández, José Luis; Moreno Juste, Antonio; Sanz Díaz, Carlos (Cuadernos de Historia Contemporánea, 2007)
Sin resumen